SWOT ANALYSIS OF REGIONAL RESILIENCE PLANNING CASE STUDY OF FLASH FLOOD IN HUMBANG HASUNDUTAN REGENCY - Feby Milanie; Abdiyanto; Muzakir Riza; Usman; Henry Paulus Lumbangaol; Elwy Asrianto Marbun; Ramayani Marpaung; Etika Siregar (PT. Radja Intercontinental Publishing, 2025)
Humbang Hasundutan Regency, North Sumatra Province, is an area with hilly topography, high rainfall, and significant land use changes. The flash floods that occurred in early 2025 in several sub-districts such as Pollung, Baktiraja, and Paranginan showed the vulnerability of this area to hydrometeorological disasters. This study aims to evaluate regional resilience planning through a SWOT analysis to determine the strengths, weaknesses, opportunities, and threats in the disaster management system in the area. The methodology used is a descriptive qualitative approach with data collection techniques through field observations, interviews with stakeholders, and review of official documents such as RTRW, RPB, and disaster reports. The results show that the existence of regional regulations and community involvement are strengths, but weak spatial planning supervision and technical capacity are major weaknesses. Opportunities such as assistance from national programs and international cooperation face threats in the form of environmental degradation and climate change. Cross-sector integration, institutional strengthening, and a participatory approach are needed to build sustainable regional resilience.